Effects of Boron and Calcium on Seed Yield and Quality of Onion: Effects of yield and quality of onion seed (Bangladesh Journal of Agriculture, 2025)
A field experiment with onion var.  BARI Piaz-1 was conducted in the research farm of Sher-e-Bangla Agricultural University, Dhaka, during the winter season (October to February) to find out the response of boron and calcium on seed yield and quality of onion. The experiment was carried out with four levels of boron viz. B0 (0 ppm), B1 (500 ppm), B2 (1000ppm) and B3 (2000 ppm); and three level of calcium viz. C0 (0 ppm), C1 (2500 ppm) and C2 (5000 ppm). This experiment was laid out in RCBD with three replications. The results showed that the treatments significantly influenced the plant height and number of leaves at all growth stages except harvesting time. At harvest, boron and calcium significantly increased the umbel per plot, flowers per umbel, fruits per umbel, fruit set (%), yield per plant, 1000-seed weight, seed yield per ha, germination and normal seedling percentage; and reduced the abnormal seedling percentage. Combined application of boron and calcium also significantly increased the all above parameters mentioned except abnormal seedling percentage of onion. The highest result of all parameters including yield showed from B3C2 but this treatment reduced production of abnormal seedling. Besides, combined of boron and calcium treatment B3C2 gave the highest plant height, leaf number and chlorophyll content. The application of 2000 ppm of boron together with 5000 ppm of calcium (B3C2) treatment gave the best performance showing the yield and quality of onion seed.Bangladesh J. Agri. 2024, 49(2): 87-100